Nietzsche and Proust a comparative study - Large, Duncan (Oxford modern languages and literature monographs., 2001)
Duncan Large combines a Nietzschean reading of Proust's novel 'A la recherche du temps perdu' with a Proustian reading of time and transcendence in Nietzsche's philosophy.